Assessment of Degree Colleges in the Transition Phase: A case study of degree colleges in the Makran Division - Manzoor Ahmed; Mehnaz Bashir; Muhammad Tariq (Journal of Education and Educational Development, 2022)
The purpose of this study was to assess the degree colleges’ preparation for the new transition phase, transferring the BA/BSc programs into ADA/ADS programs. The participants of this qualitative study were principals of Degree Colleges in the Makran division and data were collected through semi-structured interviews. Themes generated from data showed that degree colleges of the Makran division were not capable of starting the AD/ADS programs properly due to shortage of human and physical resources. The findings also identified that the principals serving these colleges were not involved in the decisions taken by Higher Education Commission for the degree colleges. Recommendations based on the findings indicate that degree colleges of the Makran region require more support and facilitation from Higher Education Commission and Provincial Government before the initiation of ADA/ADS Programs. The findings and recommendations will be helpful in the preparation of Degree colleges transferring from BA/BSc to ADA/ADS programs.
Keywords: Human resources, Physical resources, the Transition phase, ADS/ ADA programs, Principals, Degree colleges